Lessons for the future: Learning from virtual student services. Issue 176 (28th February 2022) - Hugus, Erin; Tkatchov, Mary; Becker, Brianna K.; Hunter, Kendra; Brazelton, G. Blue
Abstract: In this final article, we revisit the issue and present the common themes described throughout this issue. We conclude with recommendations for continued practice of solutions that serve all students.